Результаты детальных геофизических исследований с целью поисков скоплений углеводородов в пределах Украинского щита - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н.; Шуст, Д.Р. (Геоінформатика, 2014)
Анализируются результаты применения технологии частотно-резонансной обработки и интерпретации данных дистанционного зондирования Земли (ДЗЗ), а также геоэлектрических методов становления короткоимпульсного электромагнитного поля (СКИП) и вертикального электрорезонансного зондирования (ВЭРЗ) при поисках скоплений углеводородов (УВ) на трех поисковых участках (“Юг”, “Запад”, “Север”) в различных частях Украинского щита. В результате обработки данных ДЗЗ в пределах обследованных участков обнаружены и закартированы аномальные зоны типа “залежь нефти”, “залежь конденсата”, “залежь газа”. Аномалии подтверждены и детализированы съемкой методом СКИП. В их пределах глубины залегания аномально поляризованных пластов (АПП) типа “нефть”, “конденсат” и “газ” определены зондированием ВЭРЗ. Для всех участков по результатам детальных исследований оценены прогнозируемые ресурсы газа, газоконденсата и нефти. Для первоочередного разбуривания рекомендован поисковый участок “Север”. В его пределах выделена наиболее оптимальная зона для заложения поисковой скважины. Результаты исследований свидетельствуют, что мобильные методы могут применяться при поисках и разведке скоплений УВ в кристаллических массивах и в тектонически нарушенных (разломных) зонах кристаллического фундамента. С помощью мобильных геофизических технологий может быть выполнена оперативная оценка перспектив нефтегазоносности недостаточно изученных участков и площадей в различных регионах Украины. Проаналізовано результати застосування технології частотно-резонансної обробки та інтерпретації даних дистанційного зондування Землі (ДЗЗ), а також геоелектричних методів становлення короткоімпульсного електромагнітного поля (СКІП) і вертикального електрорезонансного зондування (ВЕРЗ) під час пошуків скупчень вуглеводнів (ВВ) на трьох пошукових ділянках (“Південь”, “Захід”, “Північ”) у різних частинах Українського щита. У результаті обробки даних ДЗЗ у межах обстежених ділянок виявлено та закартовано аномальні зони типу “поклад нафти”, “поклад конденсату”, “поклад газу”. Аномалії підтверджено та деталізовано зніманням методом СКІП. В їхніх межах глибини залягання аномально поляризованих пластів (АПП ) типу “наф¬та”, “конденсат” і “газ” визначено роботами ВЕРЗ. Для всіх ділянок за результатами детальних досліджень оцінено прогнозні ресурси газу, газоконденсату і нафти. Для першочергового розбурювання рекомендовано пошукову ділянку “Північ”. В її межах виділено найбільш оптимальну зону для закладення пошукової свердловини. Результати досліджень свідчать, що мобільні методи можна застосовувати під час пошуків і розвідки скупчень ВВ у кристалічних масивах і тектонічно порушених (розломних) зонах кристалічного фундаменту. За допомогою мобільних геофізичних технологій може бути виконана оперативна оцінка перспектив нафтогазоносності недостатньо вивчених ділянок і площ у різних регіонах України. The results of the application of technology of frequency-resonance processing and interpretation of remote sensing (RS) data
and geoelectric methods of forming short-pulsed electromagnetic field (FSPEF) and vertical electric-resonance sounding
(VERS) (FSPEF-VERS express-technology) for the hydrocarbons accumulation searching on three prospect area (“South”,
“West”, “North”) in the different parts of the Ukrainian crystalline shield are analyzed. The anomalous zone of the “oil
reservoir”, “condensate reservoir” and “gas reservoir” type was detected and mapped within all investigated areas by the
remote sensing data processing. These anomalies were confirmed and detailed by the FSPEF survey. The bedding depths of
the anomalous polarized layers (APL) of oil, gas and gas-condensate type were determined by VERS sounding within
anomalous zone. The projected resources of gas, condensate and oil have been estimated for all investigated plots by the
results of detailed studies. The site “North” is recommended for priority drilling. The optimal area for exploratory well laying
was highlighted within it. The investigation results show that mobile technologies can be used for exploration and prospecting
the hydrocarbon accumulations in crystalline massifs and tectonic fracture (fault) zones of the crystalline basement. The
operative assessment of petroleum potential of insufficiently studied sites and areas in different regions of Ukraine can be
made with mobile geophysical technologies using. The used mobile methods works within the framework of the “substantial”
paradigm of geological and geophysical studies, the essence of which is “direct” searching for a particular substance such as oil,
gas, gold, silver, platinum, zinc, iron, water, etc. FSPEF method and technology of remote sensing data processing allow
to detect and map operatively the anomalous zones of the “oil accumulation” and (or) “gas accumulation” type. The bedding
depths of the anomalous polarized layers (APL) of gas and gas-condensate type may be determined by VERS sounding within
one anomalous areas. Mobile technology allows to get a new (additional) and, more importantly, independent information on
the petroleum potential of the surveyed areas. This information, in conjunction with available geological and geophysical
materials can be used to select the objects for detailed studying and primary drilling.